Emissions reduction in the Colombian amazon: The case of caquetá - Yomayuza, Karoll Valentina (2024)
The Colombian Amazon region is a territory with unique challenges, especially in the context of climate change. The department of Caquetá has been the subject of research conducted by the Low Emissions Food Systems team of the Alliance, who analyzed the main sources of emissions in the livestock and cacao production chains, two vital products for the local and national economy.